The family in the subjective processes of LGBTQIA+ people (TEL Tempo, Espaço e Linguagem, 2023)
This study, based on the Theory of Subjectivity, aimed to comprehend the differents subjective processes of LGBTQIA+ people crossed by the family environment. Through the Constructive-Interpretive Methodology proposed by González Rey, we carried out four online conversational dynamics with a participant who understood herself as LGBT+ and who had access to the internet. Throughout the research, it was possible to establish a relationship between brazilian social subjectivity and cisheteronormativity, producing an exclusion of experiences that are outside this norm. These aspects are present within the family context and impact the subjective production of LGBTQIA+ people in different ways